Crescimento corporal e aptidão física relacionada à saúde de crianças e adolescentes - Araujo, Silvan Silva de (2006)
This study is characterized as cross-sectional, aimed to evaluate the characteristics of growth, body composition and physical fitness related to the health components in children and adolescents of district public schools in Aracaju Se. The sample was composed by 288 students from the elementary education level. 146 out of 288 are boys and 142 are girls aged between 10 and 14 years old. The data referring to the body growth was compared with national and international studies. All variables were treated through SPSS® 10.0 for Windows software, using statistical descriptive, Student t test to independent samples and variance analysis with post hoc of Newman-Keuls, test of difference between percentages of Wilcoxon (p < 0,05). The achieved results became possible to conclude that the body mass of both sexes did not present differences when compared within group throughout the researched ages. In relation to stature, comparing both sexes to the 12-year-olds, only were evidenced difference in favor of the masculine sex. The stature among the students of the masculine sex got impulse when they became 13 years old, while that in the feminine sex when they became 11 years old. The body mass among the students of the masculine sex developed itself when they became 13 years old, while that in the feminine sex when they became 11 years old. It was verified that the feminine sex presented medium values of growth variables closer to the regional, national and international studies considered than the masculine sex. The prevalence of overweight, obesity and malnutrition in both sexes were identical to the studies carried through in the northeast region. The girls had presented fat body mass higher than the one of the boys between 11 to the 14 years. This variable between student boys did not suffer variations from 10 to the 14 years, while that it between the student girls had an increment to the 14 years. The boys had presented higher lean body mass than the one of the girls to the 14 years. The lean body mass among the student of the masculine sex developed itself from the 12 years, while that in the feminine sex from the 11 years. The average levels of flexibility in the ages researched, had not significantly differed between both sexes. The abdominal strength/endurance of the subjects of the masculine sex showed itself higher than the feminine sex to the 11, 12 and 13 year-olds, while that the trength/endurance of arms this difference showed to the 12 years. The aerobic capacity of the student of the masculine sex was higher than the feminine sex to the 10, 12 and 14 years old. The maturation results showed to have influenced on the manifestation of the stature, body mass, fat body mass and VO2max in the masculine sex, while that in the feminine sex on the stature, body mass, lean body mass and fat body mass.